2021
DOI: 10.3389/fendo.2021.659268
|View full text |Cite
|
Sign up to set email alerts
|

How to Screen and Prevent Metabolic Syndrome in Patients of PCOS Early: Implications From Metabolomics

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is a complex reproductive endocrine disorder. And metabolic syndrome (MS) is an important bridge for PCOS patients to develop other diseases, such as diabetes and coronary heart disease. Our aim was to study the potential metabolic characteristics of PCOS-MS and identify sensitive biomarkers so as to provide targets for clinical screening, diagnosis, and treatment.MethodsIn this study, 44 PCOS patients with MS, 34 PCOS patients without MS, and 32 healthy controls were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…In agreement with our finding, an analysis performed by Zhao et al found that the levels of alanine, valine, serine, threonine, ornithine, phenylalanine, tyrosine, and tryptophan are generally increased and the levels of glycine and proline are reduced in plasma samples of PCOS patients . In the present study, PCOS-specific pathways, including arginine biosynthesis, , aminoacyl-tRNA biosynthesis, , beta-alanine metabolism, proline and arginine metabolism, , taurine metabolism, and phenylalanine metabolism, were activated in the ovary of the BPA lineage group, suggesting that metabolic alterations were promoted by ancestral BPA exposure effect.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our finding, an analysis performed by Zhao et al found that the levels of alanine, valine, serine, threonine, ornithine, phenylalanine, tyrosine, and tryptophan are generally increased and the levels of glycine and proline are reduced in plasma samples of PCOS patients . In the present study, PCOS-specific pathways, including arginine biosynthesis, , aminoacyl-tRNA biosynthesis, , beta-alanine metabolism, proline and arginine metabolism, , taurine metabolism, and phenylalanine metabolism, were activated in the ovary of the BPA lineage group, suggesting that metabolic alterations were promoted by ancestral BPA exposure effect.…”
Section: Discussionsupporting
confidence: 93%
“…Metabolomics approaches have been increasingly applied to interrogate molecular and metabolic alterations in metabolic diseases and are considered one of the signposts of clinical translation ( 17 , 18 ). The characterization of the metabolites that are associated with metabolic disorders may provide insights into the molecular mechanisms and define biomarkers to improve patient diagnosis, prognosis, and treatment efficacy ( 19 , 20 ). Although several studies have revealed metabolic signatures associated with obesity in humans and rodent models, there are few metabolomic profiling studies on canine obesity to date ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that an increase in glutamate levels is signi cantly associated with insulin resistance (IR) in PCOS patients [54]. Increased glutamate content in follicle can exacerbate insulin resistance in PCOS patients, resulting in a decreased fertilization rate, 2PN ssion rate, 2PN fertilization rate, and high-quality embryo rate [55].…”
Section: Amino Acid Metabolismmentioning
confidence: 99%